UPAYA PENINGKATAN AKTIVITAS SISWA DALAM PEMBELAJARAN PKN DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF JIGSAW SISWA KELAS VIII E MTSN PURWOSARI ROWOKELE SEMESTER 2 TAHUN PELAJARAN 2015/2016 - Titi Purwati (CV. Amerta Media, 2020)
The learning model used is a Jigsaw Cooperative learning model. Researcher interest in taking Jigsaw type cooperative learning models, because researchers see in Jigsaw type cooperative learning models all group members are given tasks and responsibilities, both individually and in groups. From the observations of researchers about student learning activities in class VIII-E, MTs Negeri Purwosari Rowokele Kebumen, it turns out that the Jigsaw type cooperative learning model can increase student learning activities. This can be seen by researchers from several things as follows: students can follow the learning process more passionate and enthusiastic, the emergence of students 'courage in conveying ideas or thoughts, growing student confidence in expressing their opinions, increasing students' sense of responsibility in participating in learning, very less students who roam and annoy friends. Thus the Jigsaw cooparative learning model is very suitable to be applied in the Civics learning process in MTs Negeri Purwosari Rowokele Kebumen. Key Word: learning model, Civics, Cooperative Jigsaw type